Gender, Microfinance, and Microcredit in West Africa: Empowerment for Whom?. Issue 1 (2nd January 2021) - Sackeyfio, Naaborle
ABSTRACT: Globalization, it is claimed, 'lifts all boats, and levels the playing field for economic actors and processes, while reducing the gap between the haves and have-nots. In turn, the benefits of globalization are assumed to extend the economic empowerment of women, especially those in developing countries. Yet, the dynamics of agency and autonomy amid spatialities of power and shifting modes of governance in a globalized world have produced unintended consequences which are addressed in this study. This article examines the intersection between women's empowerment, microfinance, and microcredit arrangements under globalization for Ghanaian and Nigerian women. This article argues that West African women's capacity to move beyond microfinance and microcredit institutions depends on how well they can marshal political power and economic power to become sovereign producers under globalization.